P300 brain-computer interface: comparing faces to size matched non-face stimuli. Issue 1 (2nd January 2018) - Kellicut-Jones, M. R.; Sellers, E. W.
Abstract: Non-invasive brain–computer interface (BCI) technology can restore communication for those unable to communicate due to loss of muscle control. Nonetheless, compared to augmentative and alternative communication (AAC) devices requiring muscular control, BCIs provide relatively slow communication. Therefore, implementing techniques improving BCI speed and accuracy is important. Previous studies indicate that facial stimuli elicit N170 and N400 components, in addition to the P300 component associated with P300 BCI. These additional components can increase speed and accuracy. Our study investigated the influence of image size and content using four conditions: large face, small face, large non-face, and small non-face. We predicted faces would provide higher accuracy than non-face stimuli and larger stimuli would provide higher accuracy than small stimuli. We found no significant difference in performance between conditions; however, significant waveform differences were found in each condition.